Social Support Saiyo Sakato Culture in the Management of Hypertension in Minangkabau Ethnic Group - Kurnia, Vera; Pauzi, Muhhammad; Aurura, Cindi Yunita (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Introduction: Hypertension is a major risk factor for mortality globally, nationally, and locally. Bukittinggi is one of the cities in West Sumatra that has experienced significant growth every year. Despite the high and increasing prevalence of hypertension, hypertension control remains very low due to non-compliance with treatment. One factor that influences compliance is social support, but locally-based support is still rare and limited of research. This is the basis for researcher to conduct research on social support integrated with saiyo sakato culture in the management of hypertension. Objective: to examine the correlation between saiyo sakato social support and hypertension management. Method: The study used a correlational design with a cross-sectional approach involving 38 respondents using a questionnaire that had been tested for validity and reliability, which was analyzed using Spearman's rho correlation test. Result: The showed no significant relationship between saiyo sakato-based social support with hypertension management, as evidenced by a correlation coefficient of 0.288 and a sig. (2-tailed) of 0.079. Conclusion : This was because the majority of respondents were elderly and did not have a spouse so that the assessment of nuclear family members is low. This proves that family support is very important in the management of hypertension.